The structure and composition of macrozoobenthos community in varying water qualities in Kalibaru Waters, Bengkulu, Indonesia - Lilisti LILISTI; Zamdial ZAMDIAL; Dede Hartono; Bieng Brata; Marulak Simarmata (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Lilisti, Zamdial, Hartono D, Brata B, Simarmata M. 2021. The structure and composition of macrozoobenthos community in varying water qualities in Kalibaru Waters, Bengkulu, Indonesia. Biodiversitas 22: 106-112. Various human activities affect the quality of the aquatic ecosystem that can be assessed by measuring the physical, chemical, and biological parameters of the waters and sediments. This is the case of Kalibaru Waters, Bengkulu, Indonesia which shows changes in the estuary and marine ecosystems due to the cut-off of the main river around the area for the development of roads and bridges. The objective of this study was to analyze the quality of the waters and substrate, and the structure of the macrozoobenthos community as a bioindicator at the Kalibaru Waters. A survey was carried out in four stations, which was purposively selected based on human activities around the waters. Data collected included the physical and chemical parameters, and the diversity and density of macrozoobenthos species. The density of macrozoobenthos species was analyzed for summed dominance ratio (SDR), diversity (H'), homogeneity (E), and dominance (D) indices. The results showed that the physical and chemical parameters of Kalibaru Waters were acceptable for aquatic life, however, the oil contents at two stations exceeded the ecological threshold. Analysis of the macrozoobenthos community as a bioindicator for water quality found that the diversity and homogeneity indices were at a medium level indicating an unstable community, while the dominant index remained low indicating that none of the species was dominant in the Kalibaru Waters. This information is needed as a reference for the government of Bengkulu Province to make appropriate policies and management decisions to maintain the quality of the aquatic ecosystem in Kalibaru Waters.